The Legal Framework for Surrogacy - Belabesse, Amel; Ben aziaz, Hanan (Journal of Legal Studies and Researches, 2017)
The ends justify the means—a principle the West has used to justify its excesses stemming from the interaction of technology and biomedical science with its deviant cultures. They have considered surrogacy a means to achieve motherhood without regard for religious, ethical, or legal considerations. The legal classification of this practice has been a major concern for Islamic jurisprudence. One school of thought has characterized it as a complete contract with all its legal elements and effects, while another has denied its contractual nature, arguing that surrogacy is invalid from the outset.